2023
DOI: 10.1021/acsanm.3c01249
|View full text |Cite
|
Sign up to set email alerts
|

Low-Variance Surface-Enhanced Raman Spectroscopy Using Confined Gold Nanoparticles over Silicon Nanocones

Abstract: Surface-enhanced Raman spectroscopy (SERS) substrates are of utmost interest in the analyte detection of biological and chemical diagnostics. This is primarily due to the ability of SERS to sensitively measure analytes present in localized hot spots of the SERS nanostructures. In this work, we present the formation of 67 ± 6 nm diameter gold nanoparticles supported by vertically aligned shell-insulated silicon nanocones for ultralow variance SERS. The nanoparticles are obtained through discrete rotation glanci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Recent work showed that Au nanoparticles placed on vertically aligned silicon nanocones resulted in homogeneous enhancement factors with high orders of magnitude of ∼10 8 . 30 A high enhancement factor ensures good quality sensing capabilities of a SERS substrate. Lithographic structures also give rise to homogeneity in the measured SERS signal, providing uniform results over a large area.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent work showed that Au nanoparticles placed on vertically aligned silicon nanocones resulted in homogeneous enhancement factors with high orders of magnitude of ∼10 8 . 30 A high enhancement factor ensures good quality sensing capabilities of a SERS substrate. Lithographic structures also give rise to homogeneity in the measured SERS signal, providing uniform results over a large area.…”
Section: Resultsmentioning
confidence: 99%
“…In the comparative view reported in our previous work, we see that when lithographic techniques are used, SERS signal variance can be reduced to as low as 4%. 30 For SHINERS, an additional metal oxide layer must be applied on the enhancing nanostructures to use a lithographic substrate and make it applicable for a catalytic reaction. Therefore, in approach 2, a lithographically fabricated AuNP@SiNC geometry was employed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation